Protection Coordination and Anti Islanding Protection Solution for Biomass Power Plant Connected on Distribution Network - Srete N Nikolovski; Marko Vukobratović; Ljubomir Majdandzic (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Protection coordination as well as anti-island protection play significant role in the process of biomass power plant connection on the distribution network. Distribution generation island operation in Croatia is unacceptable according to the existing National grid code Paper presents a protection coordination of all passive protections used in the real biomass power plant and connected distriubution network feeder. Short-circuits three phase, two phase and single line to ground faults and generator islanding simulations have been performed and simulated in the time domain at the different network  locations using DIgSILENT Power Factory software. The time-current plots coordination of protective devices are made using Smart PDC module in Easy Power Protector software tool.